Analysis of Learning Styles of Fourth-Grade Students at SDN 1 Sumber - Zulkarnaen, Lucky; Fikriyah, Fikriyah; Iman, Bagus Nurul (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to identify the learning styles of students visual, auditory, and kinesthetic types the teacher’s teaching style in the learning process, and students’ perceptions of the teacher’s teaching style in class IVB at SDN 1 Sumber. The research employs a qualitative approach with a descriptive method. The research subjects consist of the classroom teacher and IVB students, with data collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing. The results show that students exhibit diverse learning style tendencies, with a dominance of kinesthetic style, followed by visual and auditory. The teacher tends to use methods that more strongly accommodate the visual style, resulting in less optimal facilitation for students with other learning styles. Students’ perceptions of the teacher’s teaching vary; most respond positively to the visual explanations but are less satisfied with lessons that lack physical activities and discussions. It is concluded that aligning teaching strategies with the diversity of learning styles can enhance student engagement and understanding